2016
DOI: 10.1002/stem.2449
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor GLIS3: A New and Critical Regulator of Postnatal Stages of Mouse Spermatogenesis

Abstract: In this study, we identify a novel and essential role for the Krüppel-like zinc finger transcription factor GLI-similar 3 (GLIS3) in the regulation of postnatal spermatogenesis. We show that GLIS3 is expressed in gonocytes, spermatogonial stem cells (SSCs) and spermatogonial progenitors (SPCs), but not in differentiated spermatogonia and later stages of spermatogenesis or in somatic cells. Spermatogenesis is greatly impaired in GLIS3 knockout mice. Loss of GLIS3 function causes a moderate reduction in the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…Similar phenotypes have been observed in Glis3-deficient mice (29)(30)(31)(32)(33)(34)(35). Recently, an association was found between GLIS3 variants and congenital hypothyroidism (36).…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Similar phenotypes have been observed in Glis3-deficient mice (29)(30)(31)(32)(33)(34)(35). Recently, an association was found between GLIS3 variants and congenital hypothyroidism (36).…”
Section: Introductionsupporting
confidence: 75%
“…The level of Glis3 expression in the thyroid gland was almost equivalent to that in pancreatic islets and neonatal testis ( Figure 1C), tissues in which Glis3 is highly expressed (31,33). Moreover, analysis of the (sub)cellular localization of GLIS3 protein in the thyroid of Glis3-EGFP mice showed that GLIS3-EGFP is not expressed in PECAM1 + endothelial cells ( Figure 1D), but is expressed only in the nucleus of cells staining positively for the thyroid follicular cell marker PAX8 ( Figure 1E).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…GLIS3, interacting with its co-activator WW domain containing transcription regulator 1 (WWTR1), plays a critical role in maintaining proper renal functions (Kang et al 2009a). A recent report showed that GLIS3 is also involved in the early postnatal spermatogenesis in mice (Kang et al 2016a). In the present review, we will focus on GLIS3 and diabetes, summarizing its roles in monogenic neonatal diabetes (Table 1), T1D and T2D (Table 2), as well as the underlying mechanisms explored in animal models.…”
Section: Introductionmentioning
confidence: 99%